Sports Studies Swimming Against the Establishment of Early Childhood Mental: Sports Studies Swimming Against the Establishment of Early Childhood Mental - Dicky Hendrawan (Institute Of Computer Science (IOCS), 2020)
Sports swimming is a sport that is done in airsebagai leisure activities among the general public. Pool has benefits for the whole body motion train and exercise in breathing. Swimming motion is highly recommended for young children as the provision of body building and safety play while in the pool. Early childhood is a child referred to the latter phases of childhood aged 6-11 years (maximum 12 years) who are able to form mental operations on the knowledge they have to be able to solve the problem. Swimming sports studies on mental formation in early childhood is an attempt to discover the benefits contained in the swimming activity from the standpoint of psychology that is mental. Mental changes are influenced by the flow of blood that mixes with the adrenal gland.